Salivary Test Assessment in an Oncohematological Pediatric Sample: A Case Control Study - Matteo Saccucci; Gabriele Di Carlo; Katia Grandi; Giulia Zumbo; Luigi Stamegna; Nihad Malikzade; Fiorina Giona; Antonella Polimeni; Iole Vozza (Applied Sciences, 2022)
Background: In recent years, the incidence of neoplastic diseases in children has increased significantly. Immunodepression triggers undesirable effects in the oral cavity such as mucositis, opportunistic infections, oral bleeding, xerostomia, dysgeusia, decay, dental malformations and pain. Objective: We aim to assess, through salivary tests, the quality of saliva in pediatric patients affected by oncohematological diseases and treated with chemo/radiotherapy compared to non-treated subjects. Methods: A total of 20 subjects aged between 5 and 18 years, with oncological pathologies undergoing radio and/or chemotherapy, were evaluated. The control group consisted of 20 healthy children of the same age. The two groups of subjects were asked to undergo salivary tests. Descriptive statistics were computed for each item. Fisher’s exact test was conducted to compare case and control groups. Results: Subjects treated with chemo/radiotherapy had a lower pH and therefore a higher salivary acidity that predisposes to caries and the oral hygiene of children with oncohematological diseases was more deficient than that of the control group. Conclusions: The early detection of these indicators, and the prevention carried out to limit their severity, is an important aspect of the comprehensive care of oncohematological subjects. Pediatric dentists can play a crucial a role enabling good quality of life during cancer therapy.